Centralized versus distributed reservoirs: an investigation of their implications on environmental flows and sustainable water resources management - Eriyagama, Nishadi; Smakhtin, Vladimir U.; Udamulla, L. (Copernicus GmbH, 2018)
Storage of surface water is widely regarded as a form of insurance against rainfall variability. However, creation of surface storage often endanger the functions of natural ecosystems, and, in turn, ecosystem services that bene t humans. The issues of optimal size, placement and the number of reservoirs in a river basin – which maximizes sustainable bene ts from storage – remain subjects for debate. This study examines the above issues through the analysis of a range of reservoir con gurations in the Malwatu Oya river basin in the dry zone of Sri Lanka. The study produced multiple surface storage development pathways for the basin under different scenarios of environmental ow (EF) releases and reservoir network con gurations. The EF scenarios ranged from “zero” to “very healthy” releases. It is shown that if the “middle ground” between the two extreme EF scenarios is considered, the theoretical maximum “safe” yield from surface storage is about 65–70% of the mean annual runoff (MAR) of the basin. It is also identi ed that although distribution of reservoirs in the river network reduces the cumulative yield from the basin, this cumulative yield is maximized if the ratio among the storage capacities placed in each sub drainage basin is equivalent to the ratio among their MAR. The study suggests a framework to identify drainage regions having higher surface storage potential, to plan for the right distribution of storage capacity within a river basin, as well as to plan for EF allocations.